Ecophysiology and management of Isachne in rice fields of Onattukara - Abraham Varughese (Department of Agronomy, College of Horticulture, 1996)
Isachne miliacea Roth is the most dominant weed in the 28,000 ha of low land rice fields of the coastal sandy Onattukara region, situated in Kollam and Alapuzha districts of Kerala. A serious of investigations were undertaken at Rice Research Station, Kayamkulam, during 1991 to 1994 with the objective to identify the major weeds in the rice ecosystem and to bring out the ecophysiology of 1. Miliacea and to find out a suitable weed management strategy for the rice based cropping system of Onattukara. Isachne miliacea was found to be the dominant weed in rice during Kharif and Rabi seasons. The weed seeds germinate in April – May, attains its peak vegetative growth in July and flowers in October. The seeds mature in November and the plants dry off in January with the onset of summer. The weed is propagated by seeds and stem cuttings. Germination of seeds can be prevented by submerging the seeds in the area in water even to a depth of one centimetre. The forcing of the stem cuttings of 1. Miliacea to a depth of five centimetre below the soil surface or maintaining a submergence for more than five centimetre can effectively check the vegetative multiplication of the weed. Seeds attained physiological maturity in November and remained dormant upto March. Seeds of the season that remain on the surface germinate fully in April – May with the pre – monsoon showers while the buried seeds remain dormant. Burying the seeds to more than five centimetre depth and water stagnation in July to November induced secondary dormancy. Viability of the seeds was lost faster at shallow depth of burial. Crop weed competition studies were conducted in Kharif and Rabi for two years with different densities of 1. Miliacea. Weed competition was severe in dry dibbled Kharif compared to wet transplanted Rabi. Even a small density of five 1. Miliacea plants per square metre produced appreciable biomass and reduced the DMP of rice substantially. Integrated weed management study was conducted in Kharif and Rabi for two years in a split – plot design in three randomised blocks. Kharif season treatments formed the main plots for Rabi trial. In Kharif five pre – emergence herbicides were compared with local practice. Local practice of hoeing on 15 DAS and HW twice on 25 and 40 DAS gave maximum grain yield. Application of oxyfluorfen 0.1 kg ha-1 followed by HW on 30 DAS was on par with local practice and ranked second. The performance of other herbicides anilofos 0.40 kg, butachlor 1.25 kg and thiobencarb 1.25 kg per hectare were also satisfactory when followed by one HW on 30 DAS. Pretilachlor 0.50 kg ha-1 was phytotoxic to rice. The tested herbicides effectively controlled 1. miliacea upto harvest of rice compared to local practice. During Rabi the effect of pre-plant spray of glyphosate and hand weedings were compared. Among the treatments a pre – plant spray of glyphosate after harvest of Kharif controlled 1. miliacea best and gave maximum rice yield in Rabi season. Kharif treatments did not show any significant influence on yield of rice during Rabi. From the study it could be concluded that pre – emergence spray of oxyfluorfen 0.1 kg ha-1 followed by one HW on DAS in Kharif and pre – plant application of glyphosate 0.75 kg ha-1 on residual weeds immediately after the harvest of the Kharif crop gave efficient weed control and economic yield of rice in the rice based cropping system involving rice – rice – fallow of Onattukara region.